Climate Change and Its Impact on the Increase in Dengue Hemorrhagic Fever Cases in North Maluku Province (Case Study in Tidore Islands City) - Karim, Sarbaini A (Yayasan Ilomata, 2024)
North Maluku Province has experienced a significant increase in dengue fever cases over the past few years. The purpose of this study is to comprehensively investigate the intricate relationship between climate change and the surge in dengue fever cases in North Maluku Province. This research uses a qualitative case study approach to examine the impact of climate change on dengue fever cases in North Maluku Province. Data was analyzed through in-depth interviews with health workers, local communities, and related stakeholders using NVivo. This robust qualitative data analysis software facilitated the systematic coding, categorization, and thematic exploration of the rich insights gathered during the interviews. The findings show that climate change in this region has significantly impacted the ecology of disease vectors, rainfall patterns, and the spread and prevalence of the Aedes aegypti mosquito as the primary vector of dengue fever. Social, economic, and infrastructure factors also play an essential role in the increase in dengue fever cases. This research provides an in-depth understanding of the relationship between climate change and increased dengue fever cases in North Maluku Province. The implications of these findings underscore the urgency of implementing adaptation and mitigation strategies to address public health risks associated with climate change. This study shows climate change has increased dengue fever cases in North Maluku Province. Therefore, more effective preventive measures, coordination between institutions, and more active community participation are needed to deal with the health impacts caused by climate change.